2022
DOI: 10.3389/fmicb.2022.979790
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and genomic characterization of Salmonella enterica serovar Senftenberg isolates in production animals from the United States

Abstract: In the USA, Salmonella enterica subspecies enterica serovar Senftenberg is among the top five serovars isolated from food and the top 11 serovars isolated from clinically ill animals. Human infections are associated with exposure to farm environments or contaminated food. The objective of this study was to characterize S. Senftenberg isolates from production animals by analyzing phenotypic antimicrobial resistance profiles, genomic features and phylogeny.Salmonella Senftenberg isolates (n = 94) from 20 US stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(59 reference statements)
0
2
1
Order By: Relevance
“…The high frequency of resistance to ampicillin and ampicillin/sulbactam in our study was similar to the previous reports from China [27,29], Italy [28], and Argentina [30], suggesting that ampicillin and ampicillin/sulbactam should be carefully prescribed for clinical treatment of infections caused by such strains. In addition, resistance to sulfamethoxazole/trimethoprim in our study was lower than those in previous domestic and foreign studies [29][30][31][32], however, relatively higher than those of other studies [33,34]. The reason may lie on the regional or strain difference.…”
Section: Discussioncontrasting
confidence: 79%
“…The high frequency of resistance to ampicillin and ampicillin/sulbactam in our study was similar to the previous reports from China [27,29], Italy [28], and Argentina [30], suggesting that ampicillin and ampicillin/sulbactam should be carefully prescribed for clinical treatment of infections caused by such strains. In addition, resistance to sulfamethoxazole/trimethoprim in our study was lower than those in previous domestic and foreign studies [29][30][31][32], however, relatively higher than those of other studies [33,34]. The reason may lie on the regional or strain difference.…”
Section: Discussioncontrasting
confidence: 79%
“…In addition to the antimicrobial resistance genes, all pESI and pESI-like plasmids carried virulence genes encoding for fimbriae clusters, yersiniabactin siderophore, toxin/antitoxin systems, and resistance genes for mercury and disinfectant (15). In vitro and in vivo studies showed that the Infantis strains with the pESI-like plasmid were superior in biofilm formation, adhesion, and invasion into avian and mammalian host cells (4,16). The carriage of this plasmid by Infantis likely leads to the rapid spread of the recipient clones.…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella infections are most often caused by the consumption of contaminated dairy products, meat, eggs, as well as fruit and vegetables, which may be the result of contamination of the soil or water used in the cultivation [5]. In the USA, Salmonella enterica serovar Senftenberg is among the top five serovars isolated from food [6], and there is little information about its susceptibility to chemical disinfectants. Colibacillosis, the etiological factor of which is pathogenic Escherichia coli strains, is one of the main causes of mortality and morbidity in poultry.…”
Section: Introductionmentioning
confidence: 99%